Answer:
(3, 3 )
Step-by-step explanation:
Under a translation < 8, 0 > then
A(- 5, - 3 ) → (- 5 + 8, - 3 + 0 ) → (3, - 3 )
The line with equation y = 0 is the x- axis
Under a reflection in the x- axis
a point (x, y ) → (x, - y ), thus
(3, - 3 ) → (3, 3 )
Answer:
3
Step-by-step explanation:
just do (-1/2) x (-6) where the negatives cancels out and half of 6 is 3
Brainilist Maybe?
Answer:
The price of the cell phone without the coupon= $500
Step-by-step explanation:
Step 1: Express discounted amount
The discounted amount can be expressed as a function of the original cost of the phone as follows;
D=r×A
where;
D=discounted amount
r=coupon rate
A=original price of the cell phone before the coupon
In our case;
r=45%=45/100=0.45
A=a
replacing;
Discounted amount=(0.45×a)=0.45 a
Step 2: Amount she pays up
Amount she pays=Original cost of cell phone-discounted amount
where;
Amount she pays= $275
original cost of cell phone=a
discounted amount=0.45 a
replacing;
$275=a-0.45 a
0.55 a=275
a=275/0.55
a=500
The price of the cell phone without the coupon= $500
Answer:
24/36 = 12 x 2/12 x 3 = 2/3.
Step-by-step explanation: